"THE BANTU COMPOSERS OF SOUTHERN AFRICA”, by Yvonne Huskisson, South African Broadcasting Corporation, P.O. Box 8606, Johannesburg, South Africa; 1969; pp. 335, illus. - Tracey, Andrew (International Library of African Music, 1970)
pages: 127-128
Keywords: South Africa; African Music